Nonunion Worker Representation and the Closure of Establishments: German Evidence on the Role of Moderating Factors - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2010)
This article examines the relationship between works councils and the closure of manufacturing establishments in Germany. The relationship varies according to circumstances and type of establishment. For the subsample of single-establishment firms, the estimates show that works council presence interacts with the coverage by a collective bargaining agreement. The presence of a works council is associated with a higher probability of closure within the uncovered industrial relations regime but not within the covered regime. For establishments being parts of multi-establishment firms, works council presence is associated with a lower probability of closure. This specifically holds true if establishments face adverse economic conditions.
Keywords: J52; J53; J65; L20; L60; M54; 330; Codetermination; Collective Bargaining; Ownership Type; Competition; Plant Survival